An examination of Hegelian and Spinozian philosophy and their relationships with the International Baccalaureate subject, Theory of Knowledge - Cole, David R. (Journal of research in international education, 2005)
English One concern for teachers of the International Baccalaureate Diploma Programme is how to balance academic study with a need for the development of the imagination. This article examines the subject at the heart of the IB Diploma, Theory of Knowledge, and looks at the contrasting philosophies of Spinoza and Hegel and their relationship with this area. Through such an investigation, one may understand how the balance between academic study and the expansion of the imagination may be achieved to the benefit of the student and teacher alike. French Les enseignants du Programme du diplôme de l'Organisation du Baccalauréat International s'efforcent entre autres de trouver un certain équilibre entre l'étude théorique et le besoin de développer l'imagination. Cet article analyse la théorie de la connaissance, matière-phare du Programme du diplôme du BI et s'intéresse aux philosophies de Spinoza et Hegel, ainsi qu'à leurs relations avec cette matière. Á travers cette recherche, il est possible de comprendre comment atteindre l'équilibre entre l'étude théorique et le développement de l'imagination au profit de l'élève et de l'enseignant. Spanish Un aspecto que preocupa a los profesores del Programa del Diploma del Bachillerato Internacional es cómo encontrar un equilibrio entre el estudio teórico y la necesidad de desarrollar la imaginación. Este artículo examina Teoría del Conocimiento, materia esencial del Programa del Diploma del BI, y analiza las filosofías contrastantes de Spinoza y Hegel, así como su relación con esta materia. Mediante esta investigación, es posible entender cómo lograr el equilibrio entre el estudio teórico y el desarrollo de la imaginación para beneficio del estudiante y del propio profesor.